2018
DOI: 10.26858/jpkk.v4i1.5725
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Program Bimbingan Karir Berbasis Teori Super untuk Mengembangkan Identitas Vokasional Remaja

Abstract: The study aims to test the effectiveness of career guidance program to develop vocational identity of students. The study uses a quantitative approach with quasi experimental methods and non-equivalent pretest-posttest control group design. The study was conducted in SMK Muhammadiyah Imogiri Yogyakarta by taking a research subject that is a class XI student who is determined by random cluster sampling technique. An instrument which is used is the scale of vocational identity and observation guidelines. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Help of some kind it is very appropriate if given at school, so that each student is more develop in the maximum possible direction. Suherman (Agungbudiprabowo et al, 2018) career guidance is a process of helping a person to understand and accept a picture of himself and a picture of the world of work outside of himself, bringing that image of himself together with the world of work so that in the end he can choose a field of work, enter it and build a career in that field. In line with the above opinion career guidance is a type of guidance that tries to help individuals solve career problems, career guidance is focused on helping students understand their potential in order to develop their career life and be able to understand their role as workers and how the counselee can integrate his role as a worker with other life roles, for example his role as a family member and other things.…”
Section: Introductionmentioning
confidence: 99%
“…Help of some kind it is very appropriate if given at school, so that each student is more develop in the maximum possible direction. Suherman (Agungbudiprabowo et al, 2018) career guidance is a process of helping a person to understand and accept a picture of himself and a picture of the world of work outside of himself, bringing that image of himself together with the world of work so that in the end he can choose a field of work, enter it and build a career in that field. In line with the above opinion career guidance is a type of guidance that tries to help individuals solve career problems, career guidance is focused on helping students understand their potential in order to develop their career life and be able to understand their role as workers and how the counselee can integrate his role as a worker with other life roles, for example his role as a family member and other things.…”
Section: Introductionmentioning
confidence: 99%
“…Career success cannot be obtained without a plan and real effort. Career planning refers to an individual's activity leading to future career decision [1] [2]. Career plan plays an important role in finding one's proper location in society, making full use of one's potential ability and achieving success.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents feel they do not have experience for applying for a job, they feel lacking relevant working skill, they are lacked job information and they need to make a plan. Furthermore, a study conducted by Prabowo [1] found that there are many students who are confused with their career identity, they have not done many career exploration and commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Karenanya, tidak semua remaja telah melakukan eksplorasi dan telah menyelesaikan periode krisis dalam eksplorasi tersebut sehingga kerap kali menimbulkan kebingungan identitas (Juwitaningrum, dalam (Agungbudiprabowo et al, 2018). Kebingungan identitas ini dikarenakan pada masa remaja terjadi interaksi antara hal-hal yang sedang berkembang dalam diri remaja, seperti faktor genetik, biologis, lingkungan, juga sosial (Santrock, dalam (Agungbudiprabowo et al, 2018;Darmawani et al, 2021). Untuk mengatasi kebingungan tersebut, remaja akan mengeksplorasi berbagai hal dalam hidupnya untuk mengetahui jati dirinya (Nadiah et al, 2020).…”
unclassified
“…Kebingungan identitas ini ditemukan dalam penelitian (Agungbudiprabowo et al, 2018) bahwa profil siswa kelas XI SMK Muhammadiyah Imogiri sebelum dilakukan campur tangan dalam penelitian yakni 20 persen siswa berada pada identitas vokasional achievement, 17 persen siswa moratorium, tiga persen siswa forclosure, 60 persen siswa disfussion. Adapun (Fajri et al, 2020) menemukan bahwa profil identitas vokasional siswa XI SMKN 5 Bandung yaitu 79,8 persen siswa berada pada status identitas achievement, 5,5 persen siswa pada status identitas moratorium, 10,8 persen siswa berada pada status identitas foreclosure, dan 3,9 persen siswa berada pada status diffusion.…”
unclassified